From Hollow to Solid Carbon Spheres: Time-Dependent Facile Synthesis - Kukułka, Wojciech (Nanomaterials (Basel), 2018)
Here, we report a facile route for obtaining carbon spheres with fully tunable shell thickness. Using a hard template in chemical vapor deposition (CVD), hollow carbon spheres, solid carbon spheres, and intermediate structures can be obtained with optimized process time. The resulting carbon spheres with particle diameters of ~400 nm, as well as a controllable shell thickness from 0 to 70 nm, had high Brunauer–Emmett–Teller (BET) specific surface area (up to 344.8 m(2)·g(−1)) and pore volume (up to 0.248 cm(3)·g(−1)). The sphere formation mechanism is also proposed. This simple and reproducible technique can deliver carbon materials for various applications, e.g., energy storage and conversion, adsorption, catalytic, biomedical, and environmental applications.